Low temperature induces different cold sensitivity in two poplar clones (Populusxcanadensis Monch 'I-214' and P. deltoides Marsh. 'Dvina') - Cocozza, Claudia; Lasserre, Bruno; Giovannelli, Alessio; Castro, Gaetano; Fragnelli, Giuseppe; Tognetti, Roberto (Journal of Experimental Botany, 2009)
Changes of stem diameter were continuously monitored during winter in two field-grown poplar clones, using automatic point dendrometers. The objective of this study was to find an analytical solution to seasonal synchronization of stem diameter oscillations and low air temperatures. The study identified to what extent and with what frequency low air temperature induced stem diameter variation in ‘Dvina’ ( P. deltoides ) and ‘I-214’ ( Populus × canadensis ) poplar clones, after exposure to summer drought. The patterns of reversible stem shrinkage were related to the cycles of low air temperature. Hourly and daily evidence showed that ‘I-214’ was more sensitive to low air temperatures than ‘Dvina’. The analysis of raw data and graphic details implemented with the study of derivative tests allowed an increase in the general sensitivity of the investigation applied to describe the response of poplar clones to environmental conditions. Given these diameter fluctuation patterns, automatic point dendrometers were confirmed to be a reliable non-invasive method for testing the sensitivity of diameter variation to cold temperature. Variation in rate and duration of daily stem shrinkage in response to low air temperature in winter appeared to occur independently of the effects of water deficit suffered by plants the previous summer.